Efektivitas Model Creative-Scientific Decision Making Skills (CSDMS) Berbasis Articulate Storyline untuk Meningkatkan Berpikir Kritis dan Kreativitas Ilmiah Siswa - Asister Fernando Siagian; Muktar B. Panjaitan; Aprido Bernando Simamora; Sri Astutik Handayani (Postgraduate, University of Mataram, 2026)
The conventional learning process makes students easily bored during lessons, so their critical thinking skills and scientific creativity end up being low. Therefore, teachers need to create a learning model that’s engaging and can boost students’ motivation to learn, so their critical thinking skills and creativity improve as well. This study aims to find out how effective the Creative-Scientific Decision-Making Skills (CSDMS) model based on Articulate Storyline is in enhancing students' critical thinking skills and scientific creativity through science lessons. The research sample consisted of 28 students from SMP Negeri 3 Jorlang Hataran for a limited trial, and 56 students for a broader trial (SMP Negeri 025 Siborutorop and SMP Negeri 2 Lima Puluh Pesisir). This study is a development research (R&D) using the ADDIE model. This study used a One Group Pre-test – Post-test design. The data analysis technique in this research was by comparing students' pre-test and post-test scores using normalized gain (n-gain). It was concluded that the CSDMS model is considered effective in improving students' critical thinking skills and scientific creativity. The study results showed that the average n-gain for critical thinking skills in the limited trial was 0.83, categorized as high, and in the wide trial it was 0.92, categorized as high. Meanwhile, the average scientific creativity of students in the limited trial was 0.71, categorized as high, and in the wide trial it was 0.73, categorized as high. It was concluded that the CSDMS model is considered effective in enhancing students' critical thinking skills and scientific creativity. The challenges faced in this research are limited time, an inadequate internet connection, and the e-module in using the Articulate Storyline application still needs some minor revisions.